Potential Issues and Costs Associated with Verifying CO2 Storage During and After CO2-EOR. (July 2017) - Godec, Michael L.; Riestenberg, David; Cyphers, Shawna
Abstract: Numerous legal and regulatory frameworks in the U.S. and globally are acknowledging the opportunity for greenhouse gas (GHG) reductions provided by combining the long-term storage of CO2 in association with carbon dioxide enhanced oil recovery (CO2 -EOR), or in implementing a CO2 storage project after completion of CO2 -EOR operations. These include the U.S. Environmental Protection Agency (EPA), the International Organization for Standardization (ISO), the State of California, and the Intergovernmental Panel on Climate Change (IPCC), among many. One objective of this paper is to characterize the potential issues and estimated costs associated with adapting a CO2 -EOR project to enable it to get "credit" for stored CO2, as well as for converting a CO2 -EOR project to a "pure" CO2 storage project. Several scenarios are considered in terms of the acceptable activities that a CO2 -EOR operator would need to pursue to get "credit" for stored CO2, as well as for what would be required for converting a CO2 -EOR project to a CO2 storage project. These potential scenarios are applied to several fields currently undergoing CO2 -EOR operations to approximate a "real world" assessment of the potential implementation of this strategy. Two facilities were assumed for this assessment, based on representative CO2 -EOR projects in the Permian Basin of West Texas and Gulf Coast of the U.S. For each, two regulatory scenarios were considered for verifying and documenting CO2 storage – a Reference Case and a Stringent Case. For the cases assuming CO2 storage with CO2 -EOR, only the incremental costs associated with verifying and documenting CO2 storage are considered. Twenty years of injection are assumed, with 73 million metric tons of injected and stored CO2 assumed for the Permian Basin case, and 27 million metric tons assumed for the Gulf Coast case. A ten-year post-injection site care (PISC) period is assumed. Total project expenditures for verifying/documenting CO2 storage, on the basis of total expenditures (undiscounted) per metric ton of stored CO2, equate to $1.64/metric ton in the Reference Case, and $4.18/metric ton for the Stringent Case. For the cases assuming CO2 storage after CO2 -EOR, it is important to keep in mind that MRV costs represent only a portion of overall storage costs. In most cases, a large portion (in fact, the majority) of the costs associated with CO2 storage project in a converted CO2 -EOR project are those associated with operating the wells, equipment, and surface facilities. For this scenario, in the Reference Case, a 10-year PISC phase is assumed, while in the Stringent Case, a 50-year PISC period is assumed. For the Permian Basin case, total project expenditures for CO2 storage after CO2 -EOR $9.02/metric ton in the Reference Case, and $21.13/metric ton for the Stringent Case. For the Gulf Coast setting, total project expenditures for CO2 storage after CO2 -EOR are $5.21/metric ton in the Reference Case and $12.09/metric ton for the Stringent Case. Finally, potential conflicts between USEPA requirements and state-level mineral property, resource conservation, and environmental law in the United States remain a concern, and will need to be addressed.